Evaluation of Trends in Influenza A and B Viruses in Wastewater and Human Surveillance Data: Insights from the 2022–2023 Season in Italy - P. Mancini; D. Brandtner; C. Veneri; G. Bonanno Ferraro; M. Iaconelli; S. Puzelli; M. Facchini; G. Di Mario; P. Stefanelli; L. Lucentini; A. Muratore; Paolo Torlontano; et al. (Food and Environmental Virology, 2025)

BeyondⓇ extender in donkey semen: evaluation at 5 °C and 17 °C over 7 days - M. Caldevilla; D. Neild; A. Ferrante; I. Cáceres Monie; C. Arraztoa; J. Plaza; J. Otero; M. Gambarotta; M. Miragaya (Journal of Equine Veterinary Science, 2025)

Tracking the Spread of the BA.2.86 Lineage in Italy Through Wastewater Analysis - C. Veneri; D. Brandtner; P. Mancini; G. Bonanno Ferraro; M. Iaconelli; E. Suffredini; M. Petrillo; G. Leoni; V. Paracchini; B. M. Gawlik; A. Marchini; Paolo Torlontano; et al. (Food and Environmental Virology, 2024)
The emergence of new SARS-CoV-2 variants poses challenges to global surveillance efforts, necessitating swift actions in their detection, evaluation, and management. Among the most recent variants, Omicron BA.2.86 and its sub-lineages have gained attention due to their potential immune evasion properties. This study describes the development of a digital PCR assay for the rapid detection of BA.2.86 and its descendant lineages, in wastewater samples. By using this assay, we analyzed wastewater samples collected in Italy from September 2023 to January 2024. Our analysis revealed the presence of BA.2.86 lineages already in October 2023 with a minimal detection rate of 2% which then rapidly increased, becoming dominant by January 2024, accounting for a prevalence of 62%. The findings emphasize the significance of wastewater-based surveillance in tracking emerging variants and underscore the efficacy of targeted digital PCR assays for environmental monitoring.

Indoor quality-oriented approach for the performance evaluation of building retrofit with façade transformation: Case study of student dormitory in Mediterranean climate - A. Gigante; D. Papadaki; C. Mazzoli; V. Ntouros; R.F. De Masi; M.-N. Assimakopoulos; Annarita Ferrante (Energy and Buildings, 2024)

Evaluation of equine semen frozen in extenders free of animal proteins - Mariana L Caldevilla; Alejandro A Ferrante; Camila Tossici; Julieta C Otero; Mariana C Gambarotta; Claudia C Arraztoa; Marcelo H Miragaya; Deborah M Neild (Journal of Equine Veterinary Science, 2023)

Wastewater surveillance of SARS-CoV-2 variants in October–November 2022 in Italy: detection of XBB.1, BA.2.75 and rapid spread of the BQ.1 lineage - G. La Rosa; D. Brandtner; G. Bonanno Ferraro; C. Veneri; P. Mancini; M. Iaconelli; L. Lucentini; C. Del Giudice; L. Orlandi; Achille Palma; Adelaide Calabria; Agnese Carnevali; et al. (Science of The Total Environment, 2023)

The interactions of age, sex, body mass index, genetics, and steroid weight-based doses on tacrolimus dosing requirement after adult kidney transplantation - P. Stratta; M. Quaglia; T. Cena; R. Antoniotti; R. Fenoglio; A. Menegotto; D. Ferrante; A. Genazzani; S. Terrazzino; C. Magnani (European Journal of Clinical Pharmacology, 2012)

Cadmium Accumulation and Antioxidant Responses in Sparus aurata Exposed to Waterborne Cadmium - T. Cirillo; R. Amodio Cocchieri; E. Fasano; A. Lucisano; S. Tafuri; M. C. Ferrante; E. Carpenè; G. Andreani; G. Isani (Archives of Environmental Contamination and Toxicology, 2012)

Persistent Organochlorine Pollutants in Liver of Birds of Different Trophic Levels from Coastal Areas of Campania, Italy - B. Naso; D. Perrone; M. C. Ferrante; A. Zaccaroni; A. Lucisano (Archives of Environmental Contamination and Toxicology, 2003)